2021
DOI: 10.3390/ijerph18147224
|View full text |Cite
|
Sign up to set email alerts
|

Association of Microbiome with Oral Squamous Cell Carcinoma: A Systematic Review of the Metagenomic Studies

Abstract: The past decade has witnessed a surge in epidemiological studies that have explored the relationship between the oral microbiome and oral cancer. Owing to the diversity of the published data, a comprehensive systematic overview of the currently available evidence is critical. This review summarises the current evidence on the metagenomic studies on the oral microbiome in oral cancer. A systematic search was conducted in Medline and Embase databases to identify original studies examining the differences in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 59 publications
(281 reference statements)
1
18
1
Order By: Relevance
“…Evidence from our results suggested that bacteria from the Fusobacterium genus may be considered an oral carcinogenic bacteria. This generalization aligned with the observations reported in the recent reviews by Su Mun et al ( 2021 ) and Alon-Maimon et al ( 2022 ).…”
Section: Analysis Of Results and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Evidence from our results suggested that bacteria from the Fusobacterium genus may be considered an oral carcinogenic bacteria. This generalization aligned with the observations reported in the recent reviews by Su Mun et al ( 2021 ) and Alon-Maimon et al ( 2022 ).…”
Section: Analysis Of Results and Discussionsupporting
confidence: 93%
“…The need for such generalizations has been echoed in a recent systematic review by Su Mun et al ( 2021 ). This review provided a qualitative summary of the literature regarding OSCC-microbiome associations and noted the heterogeneity of both the methods and results found in this body of literature.…”
Section: Introductionmentioning
confidence: 99%
“…And so, the association between oral cancers and the residing microbiome is an interesting new direction being explored. Dysbiosis has been linked by multiple studies to the development of oral squamous cell carcinoma (31,32). Based on that and the publications described in the previous paragraph, one can see the correlation between adequate hygiene practices, dysbiosis and the development of oral cancer -and thus the ever so relevant role that prevention may play in clinical practice.…”
Section: Oral Cancermentioning
confidence: 93%
“…Information on oral microbial dysbiosis in PNI-positive carcinomas is minimal. However, the association of gut microbiota composition with perineural invasion was discussed in colorectal carcinoma ( Kinross et al, 2017 ; Scott et al, 2019 ), and a systematic review of metagenomic studies on the oral microbiome in oral cancer indicate the need to test the correlation of perineural invasion with oral microbiome ( Su Mun et al, 2021 ).…”
Section: The Influence Of Other Epigenetic Factors On the Head And Ne...mentioning
confidence: 99%